How does digitalization influence our reading and writing habits? (KULT_online, 2014)
The anthology Lesen, Schreiben, Erzählen. Kommunikative Kulturtechniken im digitalen Zeitalter gives an overview of current research regarding consequences of digitalization for the reception and production of knowledge. It includes various different analytical approaches, e.g. about the consequences of using software like Citavi for the writing process or the changes in narrating which can be seen in ‘Living Novels’. One of the merits of the anthology is the specific recommendations given in the different articles (e.g. which software to use for one's own academic writing or how to integrate new concepts of writing in teaching).